Outcomes and predictors of in-hospital mortality among patients admitted to the intensive care or step-down unit after a rapid response team activation: A retrospective cohort study - Vinicius Barbosa Galindo; Thais Dias Midega; Guilherme Martins de Souza; Fábio Barlem Hohmann; Mayara Laise Assis; Ricardo Luiz Cordioli; Roseny dos Reis Rodrigues; Gustavo Faissol Janot de Matos; Andreia Pardini; Michele Jaures; Bruno de Arruda Bravim; Claudia Regina Laselva; et al. (PLoS ONE, 2025)
Introduction It has been demonstrated that the implementation of rapid response teams (RRT) may improve clinical outcomes. Nevertheless, predictors of mortality among patients admitted to the intensive care unit (ICU) or to the step-down unit (SDU) after a RRT activation are not fully understood. Objective To describe clinical characteristics, resource use, main outcomes, and to address predictors of in-hospital mortality among patients admitted to the ICU/SDU after RRT activation. Methods Retrospective single-center cohort study conducted in a medical-surgical ICU/SDU located in a private quaternary care hospital. Adult patients admitted to the ICU or SDU between 2012 and 2020 were compared according to in-hospital mortality. A multivariate logistic regression analysis was performed to identify independent predictors of in-hospital mortality. Results Among the 3841 patients included in this analysis [3165 (82.4%) survivors and 676 (17.6%) non-survivors], 1972 (51.3%) were admitted to the ICU and 1869 (48.7%) were admitted to the SDU. Compared to survivors, non-survivors were older [76 (64–87) yrs. vs. 67 (50–81) yrs.; p < 0.001], had a higher SAPS 3 score [64 (56–72) vs. 49 (40–57); p < 0.001], and had a longer length of stay (LOS) before unit admission [8 (3–19) days vs. 2 (1–7) days; p < 0.001). Non-survivors used more non-invasive ventilation (NIV) (42.2% vs. 20.9%; p < 0.001), mechanical ventilation (MV) (36.7% vs. 9.3%; p < 0.001), vasopressors (39.2% vs. 12.3%; p < 0.001), renal replacement therapy (15.5% vs. 4.3%; p < 0.001), and blood components transfusion (34.9% vs. 14.0%; p < 0.001). Independent predictors of in-hospital mortality were the SAPS 3 score, the Charlson Comorbidity Index, LOS before unit admission, immunosuppression, respiratory rate < 8 or > 28 ipm criteria for RRT activation, RRT activation during the night shift, and the need for high-flow nasal cannula, NIV, MV, vasopressors, and blood components transfusion. Conclusion Multiple factors may affect outcomes of ICU/SDU-admitted patients after RRT activation. Therefore, efforts should be made to boost RRT effectiveness to improve patient safety.